Women in World Christianity: Building and Sustaining a Global Movement Gina A. Zurlo: Chichester: Wiley Blackwell, 2023; xvi + 384 pp, € 39,60, pb; ISBN 9781119823773 / € 28,98, e-book - Ma, Tianji (European journal of theology, 2025)
This book explores women’s contributions to the spread and preservation of global Christianity. Structured in three parts, it combines historical, theological and sociological insights, highlighting women’s leadership across traditions and continents. Drawing on quantitative data and using vivid narratives, Zurlo underscores women’s resilience amidst challenges such as gender-based violence and inequality. This interdisciplinary work not only enriches the study of world Christianity but also calls for recognition of women’s contributions to its past, present and future.